Hubungan Dukungan Teman Sebaya Dengan Self- Discipline Siswa Man Sidrap - Damayanti Darman; Ahkam Alwi; Andi Halimah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The peer support is an individual interaction among children or adolescents of the same age group, involving significant support and a relatively high level of closeness within their group. Peer support plays a crucial role in enhancing students' self- discipline. Self-discipline is the ability possessed by individuals to control, direct, and manage themselves based on the desire to create order and organization in life. This study aims to determine the relationship between peer support and students' self- discipline. It adopts a quantitative method with 201 research subjects, comprising 96 males (47.8%) and 105 females (52.2%) aged between 15 to 18 years old. The results reveal a positive correlation between peer support and students' self-discipline at MAN Sidrap, with a correlation value of 0.223 and a significance value of 0.01. Furthermore, the research also identifies a difference in self-discipline between males and females, with females demonstrating higher levels of self-discipline compared to males. Peer support and MAN Sidrap students' self-discipline is categorized as moderate and the results of the descriptive analysis show a positive relationship between peer support and self-discipline.